Compensation for Non-Economic Loss, the Tort-Liability Insurance System, and the 21st Century - Henderson, Roger (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1998)
Tort awards for non-economic loss have grown in an almost geometric progression in the United States since first recognized nearly 150 years ago. Not only have courts constantly expanded the areas in which claimants are permitted to recover pain and suffering awards, but at the same time they have liberalized the definition of pain and suffering itself This may be traced in part from the way the judicial system was designed after the American Revolution, the role of lawyers in the system, and the affluence of the country. Consequently, awards for non-economic loss have taken on ever increasing importance, an importance that does not bode well for the prospects for future adoptions of no-fault auto insurance plans that would curtail such recoveries. This article sketches historical influences on the tort-liability insurance system and summarizes modern developments in the law of damages for non-economic loss in the United States. It then raises questions regarding the prospects for adoption of the federal Choice No-Fault Auto Reform Act now pending in the U.S. Congress, a plan that would offer auto accident victims the choice of being compensated on a no-fault basis, while waiving their right to recover for pain and suffering. It concludes by offering a possible scenario of how future efforts to reform the tort-liability system in the United States may occur as we move into the 21st century.